THE VALUE-PRAGMATIC DIMENSION OF UKRAINE’S EUROPEAN INTEGRATION - Чабанна, Маргарита (SWorldJournal, 2025)
The article examines the evolution of public support for European integration in Ukraine and highlights the interplay between rational expectations and value-based identity motivations that shape citizens’ attitudes toward EU membership. Particular atten